Direct shoot organogenesis and plant regeneration from hypocotyl explants in selected genotypes of Leucaena leucocephala - a leguminous pulpwood tree - Sirisha, V. L.; Prashant, S.; Ranadheer, D.; Ramprasad, P.; Shaik, N. M.; Arha, Manish; Gupta, S. K.; Srivastava, Sarneer; Yadav, A. K.; Kulkarni, P. S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; et al. (Indian Journal of Biotechnology, 2008)
An efficient in vitro plant regeneration system in subabul (Leucaena leucocephala), a leguminous pulp wood tree species, was established. The induction of shoots was achieved from selected elite clones of subabul K-8, K-636 and also wild type on MS medium supplemented with 2% sucrose and different concentrations (0.88 to 24.6 mu M) of plant growth regulators (BA, Kn, 2iP & TDZ). The best medium for shoot regeneration was MS with 22.2 mu M BA (5 shoots per explant), followed by 22.7 mu M TDZ (4.6 shoots per explant). Addition of putriscine (9.3 mu M) to MS medium containing 22.2 mu M BA enhanced the number of multiple shoots to 7-8 but not the frequency of response. Shoot initials (measuring 1 cm) when separated and transferred on to MS medium containing 1.4 mu M GA(3) elongated to 2-5 cm in 15.20 d with 80% frequency. The per cent frequency of shoot differentiation was almost identical in the genotypes K-8 and K-636 but it differed significantly from the wild type. Leaf yellowing and abscission in all the genotypes was curtailed by supplementing the medium with 685 mu M glutamine or 540 mu M adenine. The excised shoots were transferred to root regeneration media containing 2.46 and 4.98 mu M IBA or 2.6 and 5.3 mu M NAA. Root regeneration was noticed with 100% frequency in all the three genotypes in presence of IBA or NAA. Plantlets were transferred successfully to the pots with 70% survival rate with no visible morphological variations. The protocol can be utilized for mass propagation and genetic transformation studies of this important pulpwood species.
Keywords: hypocotyl explants; Leucaena lucocephala; pulpwood leguminous tree; shoot organogenesis